Inside Front Cover: Volume 2 Issue 3. (30th September 2021) - Chen, Jihua; Das, Sanjib; Shao, Ming; Li, Guoliang; Lian, Huada; Qin, Jian; Browning, James F.; Keum, Jong K.; Uhrig, David; Gu, Gong; Xiao, Kai
Abstract : Inside front cover image : Understanding the phase separation mechanism of small‐molecule semiconductor and polymer blends is crucial for optimizing the phase morphology for high performance solution‐processing organic electronics. In this article, the phase morphologies of small‐molecule/polymer films formed by blending a small molecule organic semiconductor with the polystyrene with different chain architectures for organic field‐effect transistors were investigated by the combined in‐plane and out‐of‐plane techniques across multiple length scales and correlated with the device performances. Molecular dynamics modelling reveals the phase morphology is kinetically determined, limited by the inherent slow movement of polymer macromolecules. This work will guide further optimization of blend‐based organic electronics, such as OFETs and organic photovoltaics. (DOI: https://doi.org/10.1002/smm2.1036 )